Pd/In-based catalysts for nitrate catalytic removal from water: synthesis designs aiming for better N2 selectivity. Issue 2 (31st January 2023) - Sacco, Nicolas Alejandro; Miranda Zoppas, Fernanda; Aghemo, Vanina; Beltrame, Thiago; Marchesini, Fernanda Albana
Abstract: Catalysts based on Pd/In were prepared through the wet impregnation method using Al2 O3, SiO2, and TiO2 as supports. The impact of the synthesis procedure on N2 selectivity was studied. Characterization was performed using X-ray fluorescence and scanning electron microscopy–energy dispersive spectroscopy analysis. The catalytic performance of these materials was evaluated for nitrate removal from water in a batch reactor. The order of better nitrate removal was found to be Al2 O3 >TiO2 >SiO2 . The selectivity towards N2 was also impacted by the support used, with Al2 O3 -based catalysts being the most selective and TiO2 -based the least due to strong metal–support interaction. The synthesis stages also impacted nitrate removal efficiency and selectivity, with the highest N2 selectivity (94.4% at 90% nitrate conversion) found in catalysts where In was added after Pd and underwent intermediate calcination, reduction and final reduction stages. HIGHLIGHTS: Pd, In-based catalysts were prepared on different supports by varying sequential synthesis steps aiming for higher N2 selectivity in nitrate reduction. Total nitrate conversion was obtained using Pd, In/Al2 O3 and Pd, In/TiO2 . The catalytic performance was influenced by the support used in the synthesis. Pd, In/Al2 O3 was the most selective to N2 . PACRIR synthesis was the most suitable for the catalytic removal of nitrate from water. Graphical Abstract